2008
DOI: 10.1007/s10551-008-9875-0
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analytic Investigation of Business Ethics Instruction

Abstract: ethics, business ethics, ethics instruction, ethics training, training effectiveness, meta-analysis,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
138
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(152 citation statements)
references
References 79 publications
9
138
0
5
Order By: Relevance
“…However, it is hard to argue that an un-generous or non-cooperative behavior is also unethical, which perhaps leads to a disconnect between the topic of lecture and the outcome of interest. Waples et al (2009) conduct a meta-analysis that shows there is, if any, a minimal impact of ethics courses on outcomes. In a related study, Antes et al (2010) find that a course on responsible conduct of research has little impact on actual ethical decisions scientists take.…”
mentioning
confidence: 99%
“…However, it is hard to argue that an un-generous or non-cooperative behavior is also unethical, which perhaps leads to a disconnect between the topic of lecture and the outcome of interest. Waples et al (2009) conduct a meta-analysis that shows there is, if any, a minimal impact of ethics courses on outcomes. In a related study, Antes et al (2010) find that a course on responsible conduct of research has little impact on actual ethical decisions scientists take.…”
mentioning
confidence: 99%
“…This previous research found that successful teaching interventions consisted of four key components-brief standardized sessions that focus on fundamental rules and principles by employing tools such as case-based learning and cognitive strategies. 43 The library instruction in this study contained all of these components, and the results indicate that we were successful not only in introducing plagiarism concepts but in changing student perceptions of ethics related to plagiarism.…”
mentioning
confidence: 70%
“…Over the past decade, ethics instruction has become an accepted part of the business school curriculum at both the undergraduate and graduate levels (Waples et al 2009). A recent study by Litzky and MacLean (2011) shows that approximately 70 % of the top business schools have some form of an ethics course in their curricula.…”
Section: Business Ethics Educationmentioning
confidence: 99%